Determinants of Inflation Expectations - Richhild Moessner (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper analyses the determinants of short-term inflation expectations based on surveys of professionals, using dynamic cross-country panel estimation for a large number of 34 OECD economies. We find that food consumer price inflation and depreciations of the domestic exchange rate have significant positive effects on professionals' survey-based inflation expectations. Moreover, core consumer price inflation and the output gap have significant positive effects.
Keywords: E52; E58; 330; inflation expectations; inflation; food prices; exchange rates